Behaviors and Risks for Cardiovascular Disease Among Muslim Women in the United States - Henna Budhwani; Seth Borgstede; Aarin L. Palomares; Roman B. Johnson; Kristine R. Hearld (Mary Ann Liebert, 2018)
Purpose: This study examines statistical associates of cardiovascular disease risk factors, as defined by the American Heart Association's Life's Simple Seven, among Muslim women who reside in the United States. Methods: Data collected nationally through the 2015 Muslim Women's Health project were analyzed (N=373). Logistic regression models estimated associations between sample characteristics and diet, exercise, alcohol consumption, blood pressure, cholesterol, and weight. Results: Over half of respondents reported exercising regularly (64%) and maintaining a healthy diet (85%); 20% consumed alcohol. About 5% reported having high cholesterol, 4% had high blood pressure, and 42% reported being overweight. Perceived and experienced stigma were associated with alcohol use (odds ratio [OR]=1.085, p<0.001) and being overweight (OR=0.938, p<0.001). Married respondents had 42% lower odds of exercising and 83% lower odds of drinking alcohol. Compared to foreign-born respondents, U.S.-born respondents had 2.9 higher odds of drinking alcohol and 2.7 higher odds of having high cholesterol (OR=2.931, p<0.001; OR=2.732, p<0.01, respectively). Significant effects were also found when examining the statistical impact of of age, Islamic sect, and education on cardiovascular disease risk factors. Conclusion: With increasing focus on precision medicine, personalized healthcare, and patient-centered medical homes (all interventions designed to promote disease prevention and assist in managing chronic health conditions) better understanding the health of understudied populations is imperative to the success of these interventions. Our findings suggest countervailing forces may affect the health of American Muslim women; therefore, additional studies with this hard-to-reach population are warranted and will be informative to improving overall population health in the United States, an overarching priority for both public health practitioners and medical providers.